Implementasi Pembelajaran Bahasa Inggris di Kober Al-Ihsan Islamic School Kota Bandung - Sunny Saputri (Journal of Early Education and Parenting, 2023)
The problem in this study is that there are pros and cons that occur in society, there needs to be proof, is it really learning English in Early Childhood. The purpose of this study is to describe the learning process, success rate, constraints and solutions in learning English at Kober Al-Ihsan Islamic School. This research uses a descriptive qualitative approach with a case study method. The data sources for this study consisted of school principals, teachers, parents and students. Data collection techniques using interview techniques, observation and documentation. Data analysis techniques with reduction, display and verification. The results showed that English research at Kober Al-Ihsan Islamic School was running in an orderly, smooth and effective manner. so that children are accustomed and confident in using English, the school holds a meeting or parenting to socialize the school program. From the results of these observations it can be seen that there is success in achieving English learning at Kober Al-Ihsan Islamic School with an average level of child development developing as expected and developing very well. The obstacle faced is that it is difficult for children to distinguish between spoken and written forms. The solution offered is to give more time to learn English when coming home from school while waiting to be picked up by parents. The advice that the author can give is that learning English in early childhood can continue to be preserved and used daily in order to make Indonesian children smart, able to compete in the international world while upholding religious values and local wisdom.